2009
DOI: 10.1016/j.rmed.2009.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in the aging Swedish cystic fibrosis population

Abstract: Swedish Cystic Fibrosis (CF) care follows international guidelines in general. The only difference in our CF care package since 25 years is the physiotherapy regimen. Airway clearance therapy has since the early 1980s, from the day of diagnosis, been based upon daily physical exercise in conjunction with techniques for transporting and evacuating mucus. Postural Drainage+/-percussion and vibration has not been used in any age. The aim of this study was to evaluate our CF care package. Lung function data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 33 publications
1
31
0
1
Order By: Relevance
“…[4,[20][21][22] In a study conducted among Swedish CF patients, overall lung function was well preserved with a low rate of annual decline. However, a more rapid lung function decline was evident in the group colonised by PA. [9] Similar results were obtained in the two studies performed in the Western Cape, South Africa, [10,11] in which the study populations with CF more closely resembled the current SBAH study. Pulmonary function decline may be expected to be more significant in CF subjects living in a developing country, where healthcare resources may not be as available as in the developed world.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[4,[20][21][22] In a study conducted among Swedish CF patients, overall lung function was well preserved with a low rate of annual decline. However, a more rapid lung function decline was evident in the group colonised by PA. [9] Similar results were obtained in the two studies performed in the Western Cape, South Africa, [10,11] in which the study populations with CF more closely resembled the current SBAH study. Pulmonary function decline may be expected to be more significant in CF subjects living in a developing country, where healthcare resources may not be as available as in the developed world.…”
Section: Discussionsupporting
confidence: 90%
“…[10,15,16] The median age of the patients colonised by PA (19.9 years) in this study is significantly older than in many European centres, but this age is not the age of first colonisation. [17,18] The high rate of PA colonisation in the study subjects (51.7%) is greater than in some international studies, [9] but is comparable to local SA studies. [10,11] Even at study entry, patients who were colonised by PA had lower spirometric indices compared with patients who were not colonised at that stage (p=0.014, 0.0014 and 0.0061 for FEV 1 , FVC and FEF , respectively).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…4). The respiratory pump can be utilised even further when exercises are carried out in horizontal, rather than erect, positions, since gravity influences regional ventilation distribution and regional functional residual capacity differently in horizontal positions [15,19]. The fact that gravity has effects on mucus clearance during airway clearance therapy has been confirmed, although a study has shown that while lying on their side, most patients had better clearance effect in the dependent lung [19].…”
Section: Figurementioning
confidence: 99%
“…The results are often impressive, but to what extent patients can preserve the achieved exercise level is not discussed. It should be at least as important to assess to what extent patients can retain the effects of training, especially given that long-term studies have reported that physical exercise reduces the rate of lung function deterioration [13][14][15].…”
mentioning
confidence: 99%